Advanced Genetic Programming vs. State-of-the-Art AutoML in Imbalanced Binary Classification - Frank, Franz (2023)
Frank, F., & Bacao, F. (2023). Advanced Genetic Programming vs. State-of-the-Art AutoML in Imbalanced Binary Classification. Emerging Science Journal, 7(4), 1349-1363. https://doi.org/10.28991/ESJ-2023-07-04-021--- Data Availability Statement: Publicly available datasets were analyzed in this study. This data can be found here: https://github.com/joaopfonseca/mlresearch. ---This work was supported by a grant of the Portuguese Foundation for Science and Technology (“Fundação para a Ciência e a Tecnologia”), DSAIPA/DS/0116/2019, and project UIDB/04152/2020—Centro de Investigação em Gestão de Informação (MagIC)